2021
DOI: 10.3389/fimmu.2021.697071
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RAGE/ROCK1 Pathway in HMGB1-Induced Early Changes in Barrier Permeability of Human Pulmonary Microvascular Endothelial Cell

Abstract: BackgroundHigh mobility group box 1 (HMGB1) causes microvascular endothelial cell barrier dysfunction during acute lung injury (ALI) in sepsis, but the mechanisms have not been well understood. We studied the roles of RAGE and Rho kinase 1 (ROCK1) in HMGB1-induced human pulmonary endothelial barrier disruption.MethodsIn the present study, the recombinant human high mobility group box 1 (rhHMGB1) was used to stimulate human pulmonary microvascular endothelial cells (HPMECs). The endothelial cell (EC) barrier pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Notably, the blockade of RAGE using sRAGE attenuated the Ang II-induced increase in endothelial hyperpermeability (Jeong et al, 2019). A recent study reported similar findings regarding the HMGB-1-RAGE axis enhancing barrier permeability in human pulmonary microvascular endothelial cells (Zhao et al, 2021). Sepsis-associated acute kidney injury is a common complication in hospitalized and critically ill patients.…”
Section: Rage Mediates Endothelial Permeability In Diabetic Conditionsmentioning
confidence: 70%
“…Notably, the blockade of RAGE using sRAGE attenuated the Ang II-induced increase in endothelial hyperpermeability (Jeong et al, 2019). A recent study reported similar findings regarding the HMGB-1-RAGE axis enhancing barrier permeability in human pulmonary microvascular endothelial cells (Zhao et al, 2021). Sepsis-associated acute kidney injury is a common complication in hospitalized and critically ill patients.…”
Section: Rage Mediates Endothelial Permeability In Diabetic Conditionsmentioning
confidence: 70%
“…Disulfide-HMGB1 secreted can then potentially mediate a positive feedback loop by binding to TLR4 and initiating a downstream pro-inflammatory signaling cascade, which can further induce cell death. In addition, HMGB1 disrupts the integrity of the endothelial barrier through the advanced glycation end products/Rho-associated kinase 1 pathway, which induces stress fiber formation in the short term via phosphorylation of the myosin light chain [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The released HMGB1 can further activate endothelial cells, leading to up-regulation of the cell adhesion molecules ICAM-1, VCAM-1, and E-selectin, and is involved in the cytokine secretion in cells ( 37 , 38 ). The released HMGB1 has also been found to induce early EC barrier disruption, with a potential molecular mechanism being activation of the RhoA/ROCK1 signaling pathway by HMGB1 via RAGE ( 39 ). These similarities between HMGB1 and histamine in the regulation of cell inflammatory and endothelial cell permeability indicate a possible relationship between them in the vascular system.…”
Section: Discussionmentioning
confidence: 99%